2019
DOI: 10.1080/02701367.2018.1563278
|View full text |Cite
|
Sign up to set email alerts
|

Parental Behavior, Cognitive Appraisal, and Motivation in Young Athletes

Abstract: This study tested two hypotheses relating young athletes' sports motivations to parental behaviors and cognitive appraisal: (1) young athletes' motivation in sports is related to their parents' behavior; and (2) this relationship is mediated by cognitive appraisal, even after controlling for competitive level and sports records. Method: This cross-sectional study included 673 young athletes and it measured the athletes' perceptions of parental behaviors, cognitive appraisal, and sports motivation. Results: Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
(64 reference statements)
0
15
0
1
Order By: Relevance
“…The obtained results from our research, as a who le, confirm the data in literature, but reveal a certain specificity in Bulgarian conditions. The re lation between Parent-Initiated Motivational Cli mate, Perceived Motivational Climate and Goal orientation (Veskovic at al., 2013;Kolayis at al., 2017;Gomes at al., 2019, Atkins, et al, 2015Davies, Babkes, Nichols, & Coleman, 2016;O'Rourke, et al, 2013O'Rourke, et al, , 2014 is confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results from our research, as a who le, confirm the data in literature, but reveal a certain specificity in Bulgarian conditions. The re lation between Parent-Initiated Motivational Cli mate, Perceived Motivational Climate and Goal orientation (Veskovic at al., 2013;Kolayis at al., 2017;Gomes at al., 2019, Atkins, et al, 2015Davies, Babkes, Nichols, & Coleman, 2016;O'Rourke, et al, 2013O'Rourke, et al, , 2014 is confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…(Knight & Holt, 2014) berpendapat bahwa perhatian terbatas telah diberikan pada hubungan antara tujuan anak-anak dan preferensi mereka untuk keterlibatan orang tua. (Gomes et al, 2019) juga sejalan yang menghasilkan penelitian bahwa dimensi perilaku orang tua dalam olahraga berkorelasi positif satu sama lain.…”
Section: Pembahasanunclassified
“…With the stress of competition, it is important for the athlete to have a confident and positive mental state even during training 11 . There are also many external factors such as criticism and expectations that can negatively affect athletes as well 12 . Isolating yourself for the purpose of fixating on your goal can be considered the main challenge for an athlete to be successful 13 .…”
Section: Introductionmentioning
confidence: 99%